Mr. and miss anonymous ebook - Michaels, Fern (Kensington, 2012)
"Fast-moving. . .Entertaining. . .a roller-coaster ride of serendipitous fun." — Publishers Weekly Hope Lies In The Past Like many college students struggling to get by, Lily Madison and Peter Kelly help pay for tuition by making donations to a local fertility clinic. One day they meet each other at the clinic and find they have more in common than their mutual attraction, like the odd feeling all is not as it seems at the clinic. But their meeting is brief and Lily and Pete go their separate ways. Twenty years later, Pete, now a wealthy entrepreneur, sees Lily in an airport and instantly falls for her all over again. While they enjoy their unlikely reunion, a story on the news captures their attention: the disappearance of two teenage boys may be linked to the fertility clinic Pete and Lily visited in college. In a shocking twist, one of the boys looks exactly like Pete. . .